2015
DOI: 10.5194/acpd-15-23051-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Delivery of anthropogenic bioavailable iron from mineral dust and combustion aerosols to the ocean

Abstract: Abstract. Atmospheric deposition of anthropogenic soluble iron (Fe) to the ocean has been suggested to modulate primary ocean productivity and thus indirectly affect the climate. A key process contributing to anthropogenic sources of soluble Fe is associated with air pollution, which acidifies Fe-containing mineral aerosols during their transport and leads to Fe transformation from insoluble to soluble forms. However, there is large uncertainty in our estimate of this anthropogenic soluble Fe. Here, we, for th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(77 citation statements)
references
References 83 publications
(197 reference statements)
5
72
0
Order By: Relevance
“…This study uses the Integrated Massively Parallel Atmospheric Chemical Transport model [ Rotman et al , ; Liu et al , ; Feng and Penner , ; Ito et al , , , , , ; Lin et al , ; Xu and Penner , ; Ito , ; Ito and Shi , ]. The model is driven by assimilated meteorological fields from the Goddard Earth Observation System (GEOS) of the NASA Global Modeling and Assimilation Office with a horizontal resolution of 2.0° × 2.5° and 59 vertical layers.…”
Section: Model Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…This study uses the Integrated Massively Parallel Atmospheric Chemical Transport model [ Rotman et al , ; Liu et al , ; Feng and Penner , ; Ito et al , , , , , ; Lin et al , ; Xu and Penner , ; Ito , ; Ito and Shi , ]. The model is driven by assimilated meteorological fields from the Goddard Earth Observation System (GEOS) of the NASA Global Modeling and Assimilation Office with a horizontal resolution of 2.0° × 2.5° and 59 vertical layers.…”
Section: Model Approachmentioning
confidence: 99%
“…Subsequently, aging processes for Fe‐containing aerosols are dynamically simulated for the size‐segregated dust and combustion aerosols in the model, accounting for the formation of soluble Fe in aerosol water due to proton‐promoted, oxalate‐promoted, and photo‐reductive Fe dissolution schemes [ Ito , ; Ito and Shi , ]. While the Fe dissolution scheme for mineral dust was developed using laboratory measurements for Saharan dust samples, the calculation (blue triangles) reproduced the Fe release from Australian dust aerosols in acidic solution (Figure S1 in the supporting information) [ Mackie et al , ; Ito and Xu , ; Ito and Shi , ]. It should be noted that the Fe dissolution rates from mineral dust are much slower than those from combustion aerosols (red circles) [ Chen and Grassian , ; Ito , ].…”
Section: Model Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, most studies assumed 3.5% of dust was iron with a mean dust solubility of 2% [5]; however, recent studies have highlighted the importance of the various chemical states of iron in dust minerals on the solubilization rate of iron [102][103][104][105]106••]. Different mechanisms for solubilization of iron have been proposed, including photochemical-, acidic-, and organic ligand-mediated reactions [107][108][109][110][111]. Studies have also identified the potential importance of more soluble forms of iron from biomass burning, coal, and other combustion sources [84,85,112], since in some regions of the globe, long-range transported combustion iron may be quite important (for example, parts of the Southern Ocean) [44,113].…”
Section: Iron Phosphorus and Base Cationsmentioning
confidence: 99%
“…This large increase in dust may in part be explained by an anthropogenic land use source, which detailed model-data comparisons based on satellite-retrieved aerosol distributions suggest is 25% of current dust sources [120], and/or by increased aridity associated with climate change [42]. In addition, the increase in combustion iron, as well as increased acidity [110,111] from S and N emissions likely has increased the soluble iron deposition to the oceans 3-4-fold over the twentieth century [41]. Improvements in air quality in the future may reduce soluble iron deposition from combustion iron [113] although future scenarios for whether iron deposition from dust sources will increase or decrease is subject to competing processes such as increased dust due to land use change [121,122] or increased aridity [42,123], decreased dust due to wind changes [124], or some combination of these processes (Fig.…”
Section: Iron Phosphorus and Base Cationsmentioning
confidence: 99%